Pengembangan E-Modul Berbasis Flip PDF dan Canva pada Materi Transformasi Geometri - Muhammad Al Falah Kurniawan; Tri Nova Hasti Yunianta; Kriswandani Kriswandani (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
E-module is an electronic version of the module that can be used as a learning tool that contains material, methods, constraints, and ways of evaluating that are designed systematically and attractively to achieve the expected competencies. The aim of this research is develop a valid, practical, and effective e-module based on Flip PDF and Canva on the geometry transformation material. This research is an R D research using the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. The subjects of this study were 30 students of class IX SMP Negeri 9 Salatiga. Data collection techniques are observation, questionnaires, and tests. Data analysis used descriptive qualitative and quantitative analysis, Paired t-test, and N-Gain Score. The result of this research includes 1) the validation results of the e-module based on Flip PDF and Canva obtained the results of this e-module as valid as shown by the validation score of 86.155 with 90.35% and included in the "very good" category; 2) the significant of the paired t-test is 0.000 0.05 which means that there was a significant difference between the pretest score (pretest scores is 29,6667) and the posttest score (posttest score is 70,6667); and 3) the N-Gain Score test is 58,8527 (58,9%) with the criteria “effective enough.” Based on these results, it can be concluded that e-module using Flip PDF and Canva for junior high school students are effectively used as means of supporting learning materials.